Strategies in Learning English Speaking Skill at English Department Students - Afifah, Khayatul; Punama, Yulian (Universitas Pendidikan Ganesha, 2023)
The ability to speak is a factor that greatly influences the quality of a person's proficiency in conveying information orally. Base on observation among the students there were those who were clever, fast at speaking English and some were slow. It is influenced by their learning strategies. The objective of this research was to analyze learning strategies employed by the students of English Department Students (EDS) which pursue in the third grade. They were chosen based on the longer period in learning English in English Department Students (EDS). They were thirty seven students consist of twenty five girl students and 12 boy students at third grade of English Department Students (EDS). The type of this research used is one of descriptive quantitative research conducted was a survey research method. In this study, the sampling technique uses a side nonprobability system. The sample is only English skills competency students for grade who have studied English the longest so they have experienced the learning process in class with certain learning strategies. The result of the study reveals the English Department Students (EDS) students used all learning strategies, including memory, cognitive, compensation, metacognitive, affective and social. For the most frequently used by the students of the third grade is Cognitive and metacognitive strategy.